Transmission belt
Patent Information
- Application Number
- JP2021055475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0006】 本発明によれば、ベルト本体の少なくとも一部分を形成する架橋ゴム組成物が、ナノファイバとパラ系アラミド短繊維とを含有するとともに、列理方向がベルト幅方向となるように設けられ、加えて、パラ系アラミド短繊維の含有量がゴム成分100質量部に対して20質量部よりも多く、且つ25℃における列理方向の貯蔵たて弾性係数の反列理方向の貯蔵たて弾性係数に対する比が12以上であることにより高性能を得ることができる。
Smart Images

Figure 0007652606000003 
Figure 0007652606000004 
Figure 0007652606000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a power transmission belt. [Background technology]
[0002] It is known that nanofibers with a fiber diameter of 1 μm or less are used as reinforcing materials. For example, Patent Document 1 discloses that the compressed rubber layer constituting the V-side of a V-belt is formed from a crosslinked rubber composition containing a rubber component, nanofibers of polyethylene terephthalate fibers, and para-aramid short fibers. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6145170 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a high performance power transmission belt. [Means for solving the problem]
[0005] In the present invention, at least a portion of the belt body is made of a rubber component and a fiber having a diameter of 1 μm or less. Synthetic fiber A power transmission belt formed of a crosslinked rubber composition containing nanofibers and para-aramid short fibers having a fiber diameter of 10 μm or more and arranged so that the grain direction is the belt width direction, wherein the crosslinked rubber composition has a content of the para-aramid short fibers greater than 20 parts by mass per 100 parts by mass of the rubber component, and has a ratio of a storage warp elastic modulus in the grain direction to a storage warp elastic modulus in the anti-grain direction at 25° C. of 12 or more. Effect of the Invention
[0006] According to the present invention, the crosslinked rubber composition forming at least a part of the belt body contains nanofibers and para-aramid short fibers, and is arranged so that the grain direction is the belt width direction. In addition, the content of the para-aramid short fibers is more than 20 parts by mass per 100 parts by mass of the rubber component, and the ratio of the storage warp elastic modulus in the grain direction to the storage warp elastic modulus in the anti-grain direction at 25° C. is 12 or more, thereby obtaining high performance. [Brief description of the drawings]
[0007] [Figure 1A] FIG. 1 is a perspective view of a piece of a double-cogged V-belt according to an embodiment. [Figure 1B] 1 is a vertical cross-sectional view of a portion of a double-cogged V-belt according to an embodiment. [Figure 1C] FIG. 1 is a cross-sectional view of a double-cogged V-belt according to an embodiment. [Figure 2A] 1 is a cross-sectional view showing the configuration of a transmission using a double-cogged V-belt according to an embodiment. [Figure 2B] 1 is a vertical cross-sectional view showing the configuration of a transmission using a double-cogged V-belt according to an embodiment. [Diagram 3] FIG. 1 is a perspective view of a composite material. [Figure 4A] FIG. 3 is a first explanatory view of a forming and cross-linking step in the method for producing the double-cogged V-belt according to the embodiment. [Figure 4B] FIG. 4 is a second explanatory view of the forming and cross-linking step in the method for producing the double-cogged V-belt according to the embodiment. [Figure 4C] FIG. 4 is a third explanatory view of the forming and cross-linking step in the method for producing the double-cogged V-belt according to the embodiment. [Figure 4D] FIG. 4 is a fourth explanatory diagram of the forming and cross-linking step in the method for producing the double-cogged V-belt according to the embodiment. [Figure 4E] FIG. 5 is a fifth explanatory diagram of the forming and cross-linking step in the method for producing the double-cogged V-belt according to the embodiment. [Figure 4F] FIG. 6 is a sixth explanatory diagram of the forming and cross-linking step in the manufacturing method of the double-cogged V-belt according to the embodiment. [Figure 4G] FIG. 7 is a seventh explanatory diagram of the forming and cross-linking step in the manufacturing method of the double-cogged V-belt according to the embodiment. [Figure 4H] FIG. 13 is an eighth explanatory view of the forming and cross-linking step in the manufacturing method of the double-cogged V-belt according to the embodiment. [Figure 5A] FIG. 4 is a first explanatory diagram of a width-cutting / V-side surface forming step in the manufacturing method of the double-cogged V-belt according to the embodiment. [Figure 5B] FIG. 4 is a second explanatory diagram of the width-cutting and V-side forming step in the manufacturing method of the double-cogged V-belt according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The embodiments will be described in detail below.
[0009] 1A to 1C show a double cogged V-belt B (power transmission belt) according to an embodiment. The double cogged V-belt B according to the embodiment is an endless power transmission member used in, for example, a transmission for a motorcycle.
[0010] The cross-sectional shape of the double cogged V-belt B according to the embodiment is a trapezoid whose inner circumferential portion is shorter at the bottom than at the top, and a rectangular shape whose outer circumferential portion is elongated horizontally. The belt length of the double cogged V-belt B according to the embodiment is, for example, 700 mm or more and 1000 mm or less. The belt width is, for example, 10 mm or more and 36 mm or less. The belt thickness is, for example, 13 mm or more and 16 mm or less.
[0011] The inner circumferential side of the double cog V-belt B according to the embodiment is provided with a lower cog C. L are arranged at a constant pitch along the length of the belt. L The outer periphery of the vertical cross section of the double cog V-belt B according to the embodiment is formed in a sinusoidal waveform. U are arranged at a constant pitch along the length of the belt. U The outer contour of the vertical cross section is formed in a trapezoidal shape.
[0012] The double cogged V-belt B according to the embodiment includes a belt body 11 made of a rubber material, a reinforcing cloth 12 made of a fiber material, and a core wire 13. The belt body 11 has a compressed rubber layer 111 on the inner circumferential side, a tension rubber layer 112 on the outer circumferential side, and an adhesive rubber layer 113 therebetween. The reinforcing cloth 12 covers the inner circumferential surface of the compressed rubber layer 111 and is connected to the lower cog C. L The core wire 13 is embedded in the intermediate portion of the adhesive rubber layer 113 in the belt thickness direction, and is provided so as to form a spiral having a pitch in the belt width direction.
[0013] V-shaped side surfaces 111a that become pulley contact surfaces are formed on both sides of the compression rubber layer 111. The V angle in a cross section formed by the V-shaped side surfaces 111a is, for example, 27° or more and 33° or less.
[0014] The compressed rubber layer 111 which constitutes the V side surface 111a is formed of a crosslinked rubber composition X. The crosslinked rubber composition X contains a rubber component, nanofibers, and para-aramid short fibers.
[0015] Examples of the rubber component include ethylene-α-olefin elastomer (EPDM, EPR), chloroprene rubber (CR), chlorosulfonated polyethylene rubber (CSM), hydrogenated acrylonitrile rubber (H-NBR), etc. The rubber component preferably contains one or more of these, and more preferably contains ethylene-α-olefin elastomer (EPDM, EPR) or chloroprene rubber (CR).
[0016] When the rubber component contains an ethylene-α-olefin elastomer, the ethylene content is preferably 45% by mass or more and 55% by mass or less, more preferably 50% by mass or more and 53% by mass or less, from the viewpoint of obtaining excellent durability. When the rubber component contains EPDM, the diene component is preferably ethylidene norbornene (ENB) from the viewpoint of obtaining excellent durability, and the diene content (ENB content) is preferably 6% by mass or more and 12% by mass or less, more preferably 7% by mass or more and 8% by mass or less, from the same viewpoint.
[0017] When the rubber component contains an ethylene-α-olefin elastomer, the ethylene-α-olefin elastomer preferably has a Mooney viscosity of 20ML at 125° C. in order to obtain excellent kneading processability even when the compounding amount of para-aramid short fibers is large. 1+4 (125℃) or more 35ML 1+4 (125℃) or less, more preferably 25ML 1+4 (125℃) or more 30ML 1+4 When the rubber component contains chloroprene rubber, the Mooney viscosity of the chloroprene rubber at 100°C is preferably 35ML or less from the viewpoint of obtaining excellent kneading processability even when the compounding amount of para-aramid short fibers is large. 1+4 (100℃) or more 50ML 1+4 (100℃) or less, more preferably 40ML 1+4 (100℃) or more 45ML 1+4 (100°C) or less. Mooney viscosity is measured based on JIS K6300.
[0018] The nanofibers are fine fibers having a fiber diameter D1 of 1 μm or less (1000 nm or less). The fiber diameter D1 of the nanofibers is preferably 300 nm or more and 1000 nm or less, more preferably 500 nm or more and 900 nm or less. The fiber length L1 of the nanofibers is preferably 0.3 mm or more and 5 mm or less, more preferably 0.5 mm or more and 1.5 mm or less. The ratio of the fiber length L1 of the nanofibers to the fiber diameter D1 (L1 / D1: aspect ratio) is preferably 300 or more and 5000 or less, more preferably 1200 or more and 2000 or less, and even more preferably 1350 or more and 1500 or less.
[0019] Examples of nanofibers include synthetic nanofibers such as polyethylene terephthalate fibers (hereinafter referred to as "PET fibers") and polyamide fibers (6-nylon fibers, 6,6-nylon fibers), and naturally derived nanofibers such as cellulose nanofibers. The nanofibers preferably include one or more of these nanofibers, and more preferably include PET nanofibers.
[0020] The content A1 of the nanofibers in the crosslinked rubber composition X is preferably 1 part by mass or more and 5 parts by mass or less, more preferably 2 parts by mass or more and 3 parts by mass or less, based on 100 parts by mass of the rubber component. The volume content B1 of the nanofibers in the crosslinked rubber composition X is preferably 0.8 volume % or more and 1.5 volume % or less, more preferably 0.9 volume % or more and 1.1 volume % or less.
[0021] The para-aramid short fibers have a fiber diameter D2 of 10 μm or more. The para-aramid short fibers have a fiber diameter D2 of preferably 10 μm or more and 20 μm or less, more preferably 11 μm or more and 13 μm or less. The ratio (D2 / D1) of the fiber diameter D2 of the para-aramid short fibers to the fiber diameter D1 of the nanofibers is preferably 10 or more and 70 or less, more preferably 15 or more and 20 or less. The filament fineness of the para-aramid short fibers is preferably 1 dtex or more and 5 dtex or less, more preferably 1.4 dtex or more and 1.6 dtex or less.
[0022] The fiber length L2 of the para-aramid short fibers is preferably 1 mm or more and 10 mm or less, more preferably 2 mm or more and 4 mm or less. The fiber length L2 of the para-aramid short fibers is preferably longer than the fiber length L1 of the nanofibers. The ratio (L2 / L1) of the fiber length L2 of the para-aramid short fibers to the fiber length L1 of the nanofibers is preferably 1.1 or more and 5 or less, more preferably 2.5 or more and 3.5 or less.
[0023] The ratio of the fiber length L2 of the para-aramid short fibers to the fiber diameter D2 (L2 / D2: aspect ratio) is preferably 30 or more and 500 or less, more preferably 200 or more and 300 or less. The aspect ratio (L2 / D2) of the para-aramid short fibers is preferably smaller than the aspect ratio (L1 / D1) of the nanofibers. The ratio (L2 / D2 / L1 / D1) of the aspect ratio (L2 / D2) of the para-aramid short fibers to the aspect ratio (L1 / D1) of the nanofibers is preferably 0.1 or more and 0.5 or less, more preferably 0.15 or more and 0.2 or less.
[0024] Examples of para-aramid short fibers include polyparaphenylene terephthalamide short fibers and copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers. Examples of commercially available polyparaphenylene terephthalamide short fibers include Twaron manufactured by Teijin Limited, and Kevlar 29, Kevlar 49, Kevlar 119, and Kevlar 129 manufactured by DuPont. Examples of commercially available copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers include Technora manufactured by Teijin Limited. It is preferable that the para-aramid short fibers contain one or both of these. It is preferable that the para-aramid short fibers are fibrillated in the crosslinked rubber composition X to enhance the reinforcing effect, and from this viewpoint, it is more preferable that the para-aramid short fibers contain polyparaphenylene terephthalamide short fibers that are easily fibrillated.
[0025] The content A2 of the para-aramid short fibers in the crosslinked rubber composition X is more than 20 parts by mass, preferably 23 parts by mass to 40 parts by mass, more preferably 27 parts by mass to 30 parts by mass, relative to 100 parts by mass of the rubber component. The content A2 of the para-aramid short fibers is preferably more than the content A1 of the nanofibers. The ratio (A2 / A1) of the content A2 of the para-aramid short fibers to the content A1 of the nanofibers is preferably 10 to 16, more preferably 11 to 12. The sum of the contents of the nanofibers and the para-aramid short fibers (A1+A2) is preferably 24 to 45 parts by mass, more preferably 29 to 33 parts by mass, relative to 100 parts by mass of the rubber component.
[0026] The volume content B2 of the para-aramid short fibers in the crosslinked rubber composition X is preferably 10% by volume or more and 13% by volume or less, more preferably 11% by volume or more and 12.4% by volume or less. The volume content B2 of the para-aramid short fibers is preferably greater than the volume content B1 of the nanofibers. The ratio (B2 / B1) of the volume content B2 of the para-aramid short fibers to the volume content B1 of the nanofibers is preferably 8 to 15, more preferably 9 to 10. The sum of the volume contents of the nanofibers and the para-aramid short fibers (B1+B2) is preferably 10% by volume or more and 15% by volume or less, more preferably 12.5% by volume or more and 13.5% by volume or less.
[0027] In the crosslinked rubber composition X, the nanofibers and the para-aramid short fibers are dispersed in the rubber component and oriented in the grain direction. The crosslinked rubber composition X is provided such that the grain direction, which is the orientation direction of the nanofibers and the para-aramid short fibers, is the belt width direction.
[0028] The crosslinked rubber composition X may further contain a thermoplastic resin constituting the portion other than the nanofibers in the composite material described below, a reinforcing material such as carbon black, a plasticizer, a processing aid, and the like.
[0029] In the crosslinked rubber composition X, the rubber component may be crosslinked using an organic peroxide as a crosslinking agent, or the rubber component may be crosslinked using sulfur as a crosslinking agent, or the rubber component may be crosslinked using a combination of an organic peroxide and sulfur as a crosslinking agent. When the rubber component contains CR, the rubber component may be crosslinked using a metal oxide such as magnesium oxide as a crosslinking agent.
[0030] The ratio (E'1 / E'2) of the storage warp elastic modulus E'1 in the grain direction to the storage warp elastic modulus E'2 in the anti-grain direction of the crosslinked rubber composition X at 25°C is 12 or more, preferably 15 to 20, more preferably 17 to 18. The storage warp elastic modulus E'1 in the grain direction of the crosslinked rubber composition X at 25°C is measured by a tensile method based on JIS K6394:2007, with the average strain being the strain when a load 1.3 times the load at 1% strain is applied, with a strain amplitude of 0.1%, a frequency of 10 Hz, and a test temperature of 25°C. The storage warp elastic modulus E'2 in the anti-grain direction is measured by a tensile method with an average strain of 5%, a strain amplitude of 1%, a frequency of 10 Hz, and a test temperature of 25°C.
[0031] The crosslinked rubber composition X has a storage modulus E'1 in the grain direction at 25° C. of preferably 900 MPa or more and 1250 MPa or less, more preferably 1000 MPa or more and 1100 MPa or less. The storage modulus E'2 in the anti-grain direction at 25° C. is preferably 50 MPa or more and 70 MPa or less, more preferably 55 MPa or more and 65 MPa or less.
[0032] The tension rubber layer 112 and the adhesive rubber layer 113 are formed of a crosslinked rubber composition. The tension rubber layer 112 and the adhesive rubber layer 113 may be formed of the same crosslinked rubber composition X as the compression rubber layer 111.
[0033] The reinforcing fabric 12 is made of, for example, a woven fabric, knitted fabric, or nonwoven fabric made of synthetic or natural fibers. The reinforcing fabric 12 is preferably subjected to an adhesive treatment to impart adhesion to the belt body 11. Note that a reinforcing fabric of a similar configuration may be provided so as to cover the outer peripheral surface of the tension rubber layer 112 as well.
[0034] The core wire 13 is composed of twisted yarn made of synthetic fibers, etc. The core wire 13 is preferably subjected to an adhesive treatment to impart adhesiveness to the belt body 11.
[0035] In the double cogged V-belt B according to the embodiment having the above configuration, the crosslinked rubber composition X forming the compressed rubber layer 111, which is the portion constituting the V side surface 111a, contains nanofibers and para-aramid short fibers, and is provided so that the grain direction is the belt width direction. The crosslinked rubber composition X has a content A2 of para-aramid short fibers greater than 20 parts by mass relative to 100 parts by mass of the rubber component, and a ratio of the storage vertical elastic modulus in the grain direction to the storage vertical elastic modulus in the anti-grain direction at 25°C is 12 or more. This allows the double cogged V-belt B according to the embodiment to obtain high performance. Specifically, since the rigidity is relatively high in the belt width direction, the resistance to side pressure from the pulley is excellent, and since the rigidity is relatively low in the belt length direction, the bending resistance is excellent, and thus high efficiency can be obtained.
[0036] 2A and 2B show a transmission 20 for a motorcycle or the like that uses a double-cogged V-belt B according to an embodiment.
[0037] The speed change device 20 includes a drive pulley 21 and a driven pulley 22 that are arranged so that their rotation axes are parallel to each other. The double cog V-belt B according to the embodiment is wound between the drive pulley 21 and the driven pulley 22.
[0038] The driving pulley 21 and the driven pulley 22 each have a fixed sheave 211, 221 that cannot move in the axial direction, and a movable sheave 212, 222 that can move in the axial direction. A V-groove 23 into which the double-cogged V-belt B according to the embodiment fits is formed between the fixed sheave 211, 221 and the movable sheave 212, 222 in the driving pulley 21 and the driven pulley 22, respectively.
[0039] When the movable sheaves 212, 222 move toward the fixed sheaves 211, 221, the V groove 23 narrows in groove width. At this time, the double cogged V-belt B according to the embodiment is pushed up toward the outer periphery inside the V groove 23, and the winding diameter of the belt pitch lines L1, L2, i.e., the pulley diameter, increases. On the other hand, when the movable sheaves 212, 222 move away from the fixed sheaves 211, 221, the V groove 23 widens in groove width. At this time, the double cogged V-belt B according to the embodiment sinks toward the inner periphery inside the V groove 23, and the pulley diameter decreases.
[0040] With the above-described configuration, in this transmission 20, the ratio of the pulley diameters of the drive pulley 21 and the driven pulley 22 is changed between a low-speed mode in which the pulley diameter of the drive pulley 21 is small and the pulley diameter of the driven pulley 22 is large, and a high-speed mode in which the pulley diameter of the drive pulley 21 is large and the pulley diameter of the driven pulley 22 is small, thereby continuously changing and transmitting the rotational speed of the drive pulley 21 to the driven pulley 22 via the double-cogged V-belt B.
[0041] Next, a method for manufacturing the double-cogged V-belt B according to the embodiment will be described with reference to FIGS.
[0042] <Material preparation process> In the component preparation process, first, a rubber component, a composite material M having a sea-island structure of a sea of thermoplastic resin R and a large number of islands of bundles of nanofibers F as shown in FIG. 3, para-aramid short fibers, and other rubber compounding ingredients are kneaded to prepare a kneaded mass of uncrosslinked rubber composition in which the nanofibers and para-aramid short fibers are dispersed in the rubber component.
[0043] Next, the kneaded mass of the uncrosslinked rubber composition is rolled to prepare an uncrosslinked rubber sheet for forming the compressed rubber layer 111. Note that in the uncrosslinked rubber sheet, the nanofibers and the para-aramid short fibers are oriented in the grain direction, which is the rolling direction.
[0044] Here, the composite material M is a conjugate fiber in which the nanofibers F are present in parallel and independent islands in a sea polymer of a thermoplastic resin R, cut into a rod shape. The outer diameter of the composite material M is, for example, 10 μm or more and 100 μm or less. The length of the composite material M is the same as the fiber length L1 of the nanofibers F, and is preferably 0.3 mm or more and 5 mm or less, more preferably 0.5 mm or more and 1.5 mm or less.
[0045] Examples of the thermoplastic resin R include polyethylene resin, ethylene vinyl acetate copolymer resin, nylon resin, urethane resin, etc. The thermoplastic resin R preferably contains one or more of these. Since the thermoplastic resin R diffuses into the rubber component during kneading, it is preferable that the thermoplastic resin R has high compatibility with the rubber component. Therefore, when the rubber component has low polarity, the thermoplastic resin R preferably contains low polarity polyethylene resin, ethylene vinyl acetate copolymer resin, etc. In particular, when the rubber component contains ethylene-α-olefin elastomer (EPDM, EPR), the thermoplastic resin R preferably contains polyethylene resin. In addition, when the rubber component has high polarity such as nitrile rubber (NBR), the thermoplastic resin R preferably contains a highly polar polyethylene resin modified by introducing a polar group such as maleic acid, a nylon resin, a urethane resin, etc.
[0046] The content of the nanofibers F in the composite material M is, for example, 30% by mass or more and 95% by mass or less. The number of the nanofibers F in the composite material M is, for example, 10 or more and 1000 or less.
[0047] Similarly, an uncrosslinked rubber sheet for forming the tension rubber layer 112 and an uncrosslinked rubber sheet for forming the adhesive rubber layer 113 are also prepared. In addition, the reinforcing fabric 12 and the core wire 13 are each subjected to a predetermined adhesion treatment.
[0048] <Molding / crosslinking process> In the molding and cross-linking process, first, as shown in Fig. 4A, the reinforcing cloth 12 and the uncross-linked rubber sheet 111' for forming the compressed rubber layer 111 are wound in that order on the outer circumferential surface of the first cylindrical mold 311 to mold the lower cog molded body 40'. At this time, the reinforcing cloth 12 is provided so as to be aligned with the lower cog forming grooves 311a that are continuously provided in the circumferential direction on the outer periphery of the first cylindrical mold 311. Also, the uncross-linked rubber sheet 111' is provided so that its grain direction is the axial direction of the first cylindrical mold 311, and therefore the belt width direction.
[0049] Next, as shown in Fig. 4B, the lower cog molded body 40' on the first cylindrical mold 311 is covered with a first rubber sleeve 312 having a smooth inner surface, which is then placed in a vulcanizing can and sealed, and the vulcanizing can is filled with high-temperature, high-pressure steam and maintained in this state for a predetermined period of time. At this time, the uncrosslinked rubber sheet 111' flows and is pressed into the lower cog forming groove 311a, and the crosslinking proceeds to about half and is combined with the reinforcing cloth 12, forming the lower cog C on the inner periphery as shown in Fig. 4C. L A cylindrical lower cog composite 40 having the above-mentioned components formed therein is molded.
[0050] Next, steam is discharged from inside the vulcanizer to release the seal, the first cylindrical mold 311 is taken out, the first rubber sleeve 312 is removed, and the mold is cooled. Then, as shown in FIG. 4D, the outer periphery of the lower cog complex 40 molded on the first cylindrical mold 311 is cut with a blade to adjust the thickness.
[0051] Next, after the lower cog complex 40 is removed from the first cylindrical mold 311, it is fitted onto the second cylindrical mold 321 as shown in FIG. 4E. At this time, the lower cog complex 40 is fitted onto the second cylindrical mold 321. L The cog fitting grooves 321a are arranged so as to fit into the lower cog fitting grooves 321a arranged continuously in the circumferential direction on the outer periphery of the second cylindrical die 321.
[0052] Next, as shown in FIG. 4F, an uncrosslinked rubber sheet 113' for forming the adhesive rubber layer 113 is wound around the lower cog complex 40 on the second cylindrical mold 321, the core wire 13 is spirally wound around that, and then an uncrosslinked rubber sheet 113' for forming the adhesive rubber layer 113 and an uncrosslinked rubber sheet 112' for forming the tensile rubber layer 112 are wound around that in sequence to form an uncrosslinked slab S'.
[0053] Next, as shown in FIG. 4G, the uncrosslinked slab S' is covered with the second rubber sleeve 322, which is placed in a vulcanizing can and sealed, and the vulcanizing can is filled with high-temperature and high-pressure steam and maintained in that state for a predetermined time. At this time, the main crosslinking of the lower cog complex 40 progresses. At the same time, the uncrosslinked rubber sheet 113' for forming the adhesive rubber layer 113 also crosslinks and is compounded with the core wire 13. In addition, the uncrosslinked rubber sheet 112' for forming the tension rubber layer 112 flows and is pressed into the upper cog forming grooves 322a arranged in a circumferential direction on the inner circumference of the second rubber sleeve 322, and the crosslinking progresses. Then, as shown in FIG. 4H, the entirety is integrated to form a cylindrical belt slab S.
[0054] <Width cutting and V side forming process> Steam is discharged from the vulcanizer to release the seal, the second cylindrical mold 321 is taken out, the second rubber sleeve 322 is removed, and after cooling, the belt slab S is demolded from the second cylindrical mold 321.
[0055] Then, as shown in FIG. 5A, the belt slab S is cut to a predetermined width, and then, as shown in FIG. 5B, both sides are cut with a blade to form V-shaped sides 111a, thereby obtaining the double-cogged V-belt B of the embodiment.
[0056] In the above embodiment, the double-cogged V-belt B is shown, but the present invention is not limited thereto, and may be a single-cogged V-belt having only a lower cog, or may be a raw-edge V-belt having no cog. The V-ribbed belt may be a V-ribbed belt in which the V-side surface of the V-rib is formed of the crosslinked rubber composition X, and the same effects as those of the above embodiment can be obtained. Furthermore, at least a part of the belt body may be a toothed belt or a flat belt formed of the crosslinked rubber composition X, and high performance can be obtained. Specifically, in these cases, the crosslinked rubber composition X is provided so that the grain direction is the belt width direction and the anti-grain direction is the belt length direction, and since the crosslinked rubber composition X has a relatively high rigidity in the belt width direction, warping in the belt width direction can be suppressed, and since the crosslinked rubber composition X has a relatively low rigidity in the belt length direction, it can be bent with a small force and wound around a pulley, and as a result, stable belt running performance can be obtained for a long time. EXAMPLES
[0057] (Crosslinked Rubber Composition) The crosslinked rubber compositions were prepared in the following Examples 1 to 3 and Comparative Examples 1 to 4. The configurations of each are also shown in Tables 1 and 2.
[0058] <Example 1> In a Banbury mixer, EPDM (T7241 manufactured by JSR, ethylene content: 52% by mass, ENB content: 7.7% by mass, Mooney viscosity: 27ML) 1+4A mixture of 50 parts by mass of FEF carbon black (Seest SO, manufactured by Tokai Carbon Co., Ltd.), 5 parts by mass of a hydrocarbon plasticizer (Samper 2280, manufactured by Sun Oil Co., Ltd.), 1 part by mass of stearic acid as a processing aid (Stearic Acid S50, manufactured by New Japan Chemical Co., Ltd.), 5 parts by mass of zinc oxide as a vulcanization accelerator aid (Zinc Oxide 3, manufactured by Sakai Chemical Co., Ltd.), 2 parts by mass of trimethylolpropane trimethacrylate as a co-crosslinking agent (Hi-Cross M, manufactured by Seiko Chemical Co., Ltd.), and 3 parts by mass of N,N'-m-phenylene bismaleimide as a co-crosslinking agent (Bulnoc PM, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was added and kneaded relative to 100 parts by mass of the rubber component, and then 3.6 parts by mass of a composite material (polyethylene resin-PET nanofiber (Nanofront) composite material, manufactured by Teijin Frontier Corporation) was added relative to 100 parts by mass of the rubber component, and the mixture was further kneaded at a temperature higher than the melting point of the polyethylene resin contained in the composite material.
[0059] Next, the kneaded mass of the uncrosslinked rubber composition was discharged from the Banbury mixer and cooled once, and then, the kneaded mass was again charged into the Banbury mixer together with 37 parts by mass of polyparaphenylene terephthalamide short fibers (Kevlar 119, manufactured by DuPont) which are para-aramid short fibers, and 7.4 parts by mass (3 parts by mass of active ingredient) of an organic peroxide crosslinking agent (Perhexa 25B-40, manufactured by Nippon Oil & Fats Co., Ltd., purity 40% by mass) per 100 parts by mass of the rubber component, and kneaded.
[0060] Subsequently, the kneaded mass of the uncrosslinked rubber composition was discharged from the Banbury mixer, and the kneaded mass was rolled by a calendar roll to obtain an uncrosslinked rubber sheet.
[0061] The uncrosslinked rubber sheet thus obtained was press-molded to produce a sheet-shaped crosslinked rubber composition. This sheet-shaped crosslinked rubber composition was designated as Example 1.
[0062] Here, the composite material used above has a sea-island structure with a sea of polyethylene resin and islands of 1200 PET nanofibers.
[0063] The composite material contains 30% by mass of polyethylene resin and 70% by mass of nanofiber. Therefore, the content of polyethylene resin is 1.1 parts by mass and the content A1 of nanofiber is 2.5 parts by mass for 100 parts by mass of rubber component.
[0064] The outer diameter of the composite material is 30 μm and the length is 1 mm. Therefore, the fiber length L1 of the PET fiber nanofiber is 1 mm. The fiber diameter D1 is 700 nm. The fiber diameter D2 of the polyparaphenylene terephthalamide short fiber of the para-aramid short fiber is 12 μm. The fiber length L2 is 3 mm.
[0065] In the crosslinked rubber composition of Example 1, the volume fraction B1 of the nanofibers is 0.87 volume % and the volume fraction B2 of the para-aramid short fibers is 12.5 volume %.
[0066] <Example 2> A Banbury mixer was charged with EPDM as a rubber component, and 40 parts by mass of ISAF carbon black (Seast 6, manufactured by Tokai Carbon Co., Ltd.), 10 parts by mass of process oil, 0.25 parts by mass of stearic acid as a processing aid, 5 parts by mass of zinc oxide as a vulcanization accelerator aid, 4 parts by mass of N,N'-m-phenylene bismaleimide as a co-crosslinking agent, 1 part by mass of amylphenol disulfide polymer (Suncerer AP, manufactured by Sanshin Chemical Industry Co., Ltd.) as a co-crosslinking agent, and 20 parts by mass of zinc dimethacrylate (Actor ZMA, manufactured by Kawaguchi Chemical Industry Co., Ltd.) as a co-crosslinking agent were charged and kneaded relative to 100 parts by mass of the rubber component, and then 3.6 parts by mass of a composite material was charged relative to 100 parts by mass of the rubber component, and the mixture was further kneaded at a temperature higher than the melting point of the polyethylene resin contained in the composite material.
[0067] Next, the kneaded mass of uncrosslinked rubber composition was discharged from the Banbury mixer and cooled once, and then it was again charged into the Banbury mixer together with 28 parts by mass of polyparaphenylene terephthalamide short fibers of para-aramid short fibers, 0.5 parts by mass of sulfur (Seimi OT, manufactured by Nippon Kanretsu Kogyo Co., Ltd.) as a crosslinking agent, and 7 parts by mass (2.8 parts by mass of active ingredient) of an organic peroxide crosslinking agent (Peroximon F-40, manufactured by Nippon Oil & Fats Co., Ltd., purity 40% by mass), per 100 parts by mass of the rubber component, and kneaded.
[0068] Subsequently, the kneaded mass of the uncrosslinked rubber composition was discharged from the Banbury mixer, and the kneaded mass was rolled by a calendar roll to obtain an uncrosslinked rubber sheet.
[0069] The uncrosslinked rubber sheet thus obtained was press-molded to produce a sheet-shaped crosslinked rubber composition. This sheet-shaped crosslinked rubber composition was designated as Example 2.
[0070] In the crosslinked rubber composition of Example 2, the volume fraction B1 of the nanofibers is 1.06 vol. %, and the volume fraction B2 of the para-aramid short fibers is 10.11 vol. %.
[0071] <Example 3> In a Banbury mixer, rubber component CR (Skyprene 505, Tosoh Corporation, Mooney viscosity 42ML) was added. 1+4 (100°C)) was added, and 50 parts by mass of FEF carbon black, 5.4 parts by mass of DOS as an ester-based plasticizer, 0.6 parts by mass of stearic acid as a processing aid, 6 parts by mass of N,N'-m-phenylene bismaleimide as a co-crosslinking agent, and 2 parts by mass of tetramethylthiuram disulfide (Noccela TT, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) as a vulcanization accelerator were added and kneaded per 100 parts by mass of the rubber component, and then 3.6 parts by mass of a composite material was added per 100 parts by mass of the rubber component, and they were further kneaded at a temperature higher than the melting point of the polyethylene resin contained in the composite material.
[0072] Next, the kneaded mass of the uncrosslinked rubber composition was discharged from the Banbury mixer and cooled once, and then it was again charged into the Banbury mixer together with 26 parts by mass of copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fiber (Technora, manufactured by Teijin Limited) which is a para-aramid short fiber, and 5.4 parts by mass of magnesium oxide (Kyowamag 150, manufactured by Kyowa Chemical Industry Co., Ltd.) which is a crosslinking agent, per 100 parts by mass of the rubber component, and kneaded.
[0073] Subsequently, the kneaded mass of the uncrosslinked rubber composition was discharged from the Banbury mixer, and the kneaded mass was rolled by a calendar roll to obtain an uncrosslinked rubber sheet.
[0074] The uncrosslinked rubber sheet thus obtained was press-molded to produce a sheet-shaped crosslinked rubber composition. This sheet-shaped crosslinked rubber composition was designated as Example 3.
[0075] The fiber diameter D2 of the para-aramid short fiber, copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fiber, is 12 μm. The fiber length L2 is 3 mm.
[0076] In the crosslinked rubber composition of Example 3, the volume fraction B1 of the nanofibers is 1.39 volume % and the volume fraction B2 of the para-aramid short fibers is 12.4 volume %.
[0077] <Comparative Example 1> A cross-linked rubber composition sheet was prepared in the same manner as in Example 1, except that, as the para-aramid short fibers, copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers were used instead of polyparaphenylene terephthalamide short fibers, the content of the copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers was 21.4 parts by mass relative to 100 parts by mass of the rubber component, and no composite material was used. This cross-linked rubber composition sheet was designated Comparative Example 1.
[0078] <Comparative Example 2> A cross-linked rubber composition sheet was prepared in the same manner as in Example 1, except that the content of the polyparaphenylene terephthalamide short fibers of the para-aramid short fibers was 22.1 parts by mass relative to 100 parts by mass of the rubber component and no composite material was used. This cross-linked rubber composition sheet was designated Comparative Example 2.
[0079] <Comparative Example 3> A cross-linked rubber composition sheet was prepared in the same manner as in Example 1, except that the content of the polyparaphenylene terephthalamide short fibers of the para-aramid short fibers was 40 parts by mass relative to 100 parts by mass of the rubber component and no composite material was used. This cross-linked rubber composition sheet was designated Comparative Example 3.
[0080] <Comparative Example 4> A sheet-shaped crosslinked rubber composition was prepared in the same manner as in Example 3, except that no composite material was used. This sheet-shaped crosslinked rubber composition was designated Comparative Example 4.
[0081] [Table 1]
[0082] [Table 2]
[0083] (Test Method) For each of the crosslinked rubber compositions of Examples 1 to 3 and Comparative Examples 1 to 4, the strain when a load 1.3 times the load at 1% strain was applied was defined as the average strain, and the storage warp elastic modulus E'1 in the grain direction was measured by a tensile method with a strain amplitude of 0.1%, a frequency of 10 Hz, and a test temperature of 25°C, based on JIS K6394:2007. The storage warp elastic modulus E'2 in the anti-grain direction was measured by a tensile method with an average strain of 5%, a strain amplitude of 1%, a frequency of 10 Hz, and a test temperature of 25°C. The ratio (E'1 / E'2) of the storage warp elastic modulus E'1 in the grain direction to the storage warp elastic modulus E'2 in the anti-grain direction was calculated. A viscoelasticity tester manufactured by RHEOLOGY was used for the measurement.
[0084] (Test Results) The test results are shown in Table 1. According to this, it can be seen that in Examples 1 and 2, which contain EPDM as the rubber component, nanofibers, and para-aramid short fibers, E'1 / E'2 is very high. From this, if these are used to form the parts constituting the V-side of a V-belt so that the grain direction corresponds to the belt width direction and the anti-grain direction corresponds to the belt length direction, respectively, the belt width direction has a relatively high rigidity, so that resistance to side pressure from the pulley is excellent, and the belt length direction has a relatively low rigidity, so that bending resistance is excellent, and therefore high efficiency can be expected. On the other hand, it can be seen that in Comparative Examples 1 to 3, which do not contain nanofibers, E'1 / E'2 is lower than Examples 1 and 2.
[0085] Even when CR was used as the rubber component, it was found that Example 3, which contained nanofibers and para-aramid short fibers, had a very high E'1 / E'2 ratio. On the other hand, Comparative Example 4, which did not contain nanofibers, had a lower E'1 / E'2 ratio than Example 3. [Industrial Applicability]
[0086] The present invention is useful in the technical field of power transmission belts. [Explanation of symbols]
[0087] B Double-cogged V-belt (power transmission belt) C L Lower cog C U Upper cog M Composite material R Thermoplastic resin F Nanofiber S' Uncrosslinked slab S Belt Slab 11 Belt body 111 Compressed rubber layer 111', 112', 113' Uncrosslinked rubber sheet 111a V side 112 Tension rubber layer 113 Adhesive rubber layer 12 Reinforcement fabric 13 Core Wire 20 Gearbox 21 Drive pulley 211,221 Fixed sheave 212,222 Movable sheave 22 Driven pulley 23 V groove 311 First Cylinder Type 311a Lower cog forming groove 312 First rubber sleeve 321 Second cylindrical type 321a Lower cog fitting groove 322 Second rubber sleeve 322a Upper cog forming groove 40' Lower cog molding 40 Lower Cog Complex
Claims
1. A power transmission belt, at least a portion of which is made of a crosslinked rubber composition containing a rubber component, synthetic nanofibers having a fiber diameter of 1 μm or less, and para-aramid short fibers having a fiber diameter of 10 μm or more, and arranged so that the grain direction is the belt width direction, The crosslinked rubber composition for the power transmission belt has a para-aramid short fiber content of more than 20 parts by mass per 100 parts by mass of the rubber component, and a ratio of a storage warp elastic modulus in the grain direction to a storage warp elastic modulus in the anti-grain direction at 25° C. is 12 or more.
2. The power transmission belt according to claim 1, The aspect ratio of the fiber length to the fiber diameter of the nanofiber is 300 or more and 5,000 or less.
3. The power transmission belt according to claim 1 or 2, The aspect ratio of the fiber length to the fiber diameter of the para-aramid short fibers is 30 or more and 500 or less.
4. The power transmission belt according to any one of claims 1 to 3, The crosslinked rubber composition has a content of the nanofibers of 1 part by mass or more and 5 parts by mass or less per 100 parts by mass of the rubber component.
5. The power transmission belt according to any one of claims 1 to 4, The crosslinked rubber composition has a storage modulus of elasticity in the grain direction at 25° C. of 900 MPa or more.
6. The power transmission belt according to any one of claims 1 to 5, The power transmission belt is a V-belt or a V-ribbed belt.
7. The power transmission belt according to any one of claims 1 to 5, The power transmission belt is a toothed belt or a flat belt.
8. A transmission belt according to any one of claims 1 to 7, The power transmission belt, wherein the rubber component contains EPDM having an ethylene content of 45 parts by mass or more and 55 parts by mass or less, a diene component which is ethylidene norbornene, and the diene content of the diene component is 6% by mass or more and 12% by mass or less.
9. A transmission belt according to any one of claims 1 to 8, The nanofibers have a fiber diameter of 300 nm or more.
10. A power transmission belt according to any one of claims 1 to 9, The nanofibers have a fiber length of 0.3 mm or more and 5 mm or less.
11. A power transmission belt according to any one of claims 1 to 10, The power transmission belt, wherein the synthetic fiber nanofiber is a polyethylene terephthalate fiber nanofiber.
12. A power transmission belt according to any one of claims 1 to 11, The para-aramid short fibers have a fiber diameter of 20 μm or less.
13. A power transmission belt according to any one of claims 1 to 12, The para-aramid short fibers have a fiber length of 1 mm or more and 10 mm or less.
14. A power transmission belt according to any one of claims 1 to 13, A power transmission belt, wherein the para-aramid short fibers have a fiber length longer than the fiber length of the nanofibers.
15. A power transmission belt according to any one of claims 1 to 14, A power transmission belt, wherein a ratio of a fiber diameter of the para-aramid short fibers to a fiber diameter of the nanofibers is 10 or more and 70 or less.
16. A power transmission belt according to any one of claims 1 to 15, A power transmission belt, wherein a ratio of the fiber length of the para-aramid short fibers to the fiber length of the nanofibers is 1.1 or more and 5 or less.
17. A power transmission belt according to any one of claims 1 to 16, A power transmission belt, wherein a ratio of an aspect ratio of the para-aramid short fibers to an aspect ratio of the nanofibers is 0.1 or more and 0.5 or less.
18. A power transmission belt according to any one of claims 1 to 17, The para-aramid staple fibers include polyparaphenylene terephthalamide staple fibers.
19. A power transmission belt according to any one of claims 1 to 18, The content of the para-aramid short fibers in the crosslinked rubber composition is 40 parts by mass or less per 100 parts by mass of the rubber component.
20. A power transmission belt according to any one of claims 1 to 19, A power transmission belt, wherein a mass ratio of a content of the para-aramid short fibers to a content of the nanofibers is 10 or more and 16 or less.
21. A power transmission belt according to any one of claims 1 to 20, The crosslinked rubber composition has a total content of the nanofibers and the para-aramid short fibers of 24 parts by mass or more and 45 parts by mass or less per 100 parts by mass of the rubber component.
22. A power transmission belt according to any one of claims 1 to 21, A power transmission belt, wherein the ratio of the storage longitudinal elastic modulus of the crosslinked rubber composition in the grain direction to the storage longitudinal elastic modulus in the anti-grain direction at 25° C. is 20 or less.
23. A power transmission belt according to any one of claims 1 to 22, The crosslinked rubber composition has a storage modulus of elasticity in the grain direction at 25° C. of 1250 MPa or less.
24. A power transmission belt according to any one of claims 1 to 23, The crosslinked rubber composition has a storage warp elastic modulus in the anti-grain direction at 25° C. of 50 MPa or more and 70 MPa or less.
Citation Information
Patent Citations
Lubricating structure of transfer
JP1986045170A
Large v-belt
WO2020246188A1